INTERACTIVE WHITEBOARD IN EDUCATION - Milan, KLEMENT; LAVRINČÍK, Jan (Trends in education, 2009)
The article deals with the problems of interactive education in the lower secondary education. Question of the equipment classroom and installation specialize software are introduced. It present about creation of interactive education lesson for practical education. At the end it discussed about web-based portal.
Keywords: interactive whiteboard; interactive education; portal for interactive education.